2020
DOI: 10.3390/molecules25153368
|View full text |Cite
|
Sign up to set email alerts
|

Achillea millefolium L. and Achillea biebersteinii Afan. Hydroglycolic Extracts–Bioactive Ingredients for Cosmetic Use

Abstract: Studies on hydroglycolic (HG) extracts of Achillea biebersteinii (AB)—a less investigated representative of the genus—were performed to determine their potential for cosmetic applications compared to the well-known Achillea millefolium (AM). Three types of water:polyethylene glycol extracts (1:1, 4:1, 6:1 v/v) were obtained from both species and analyzed for their composition by high performance liquid chromatography coupled with mass spectrometry (HPLC-ESI-Q-TOF-MS) and assayed for their biological activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Among the analyzed compounds, 5-O-caffeoylquinic acid, 3,5-O-dicaffeoylquinic acid, isoorientin and swertiajaponin were presented in all samples in the greatest quantities. It was found that the most effective solvent in extracting phenolics in both both Cephalaria species was 80% acetone followed by mixture of methanol-acetone-water; this may be due to the lower water content and it is in agreement with the other reports [49]. The leading phenolic acids identified in both species were 5-O-caffeoylquinic acid (94.90 ± 0.42-135.83 ± 1.47 µg/g DE) and 3,5-O-dicaffeoylquinic acid (41.29 ± 0.11-118.90 ± 0.46 µg/g DE).…”
Section: Qualitative Lc-dad-ms 3 Analysis Of the Chemical Compositionsupporting
confidence: 90%
“…Among the analyzed compounds, 5-O-caffeoylquinic acid, 3,5-O-dicaffeoylquinic acid, isoorientin and swertiajaponin were presented in all samples in the greatest quantities. It was found that the most effective solvent in extracting phenolics in both both Cephalaria species was 80% acetone followed by mixture of methanol-acetone-water; this may be due to the lower water content and it is in agreement with the other reports [49]. The leading phenolic acids identified in both species were 5-O-caffeoylquinic acid (94.90 ± 0.42-135.83 ± 1.47 µg/g DE) and 3,5-O-dicaffeoylquinic acid (41.29 ± 0.11-118.90 ± 0.46 µg/g DE).…”
Section: Qualitative Lc-dad-ms 3 Analysis Of the Chemical Compositionsupporting
confidence: 90%
“…Tyrosinase inhibitory activity was also detected in extracts from aerial parts of A. monocephala, A. coarctata [ 26 ], A. phrygia [ 27 ], A. alpina [ 28 ], and A. teretifolia [ 13 ]. As previously summarized, A. biebersteinii extracts were recently reported as sources of tyrosinase inhibitors [ 13 , 14 ]. The results presented in Figure 2 confirmed previous findings, showing that most of the A. biebersteinii extracts decrease the activity of mushroom tyrosinase by 24–40%.…”
Section: Resultsmentioning
confidence: 99%
“…Methanolic extract from A. biebersteinii was recently identified as a potential source of antityrosinease compounds, with stronger mushroom tyrosinase inhibitory activity than A. millefolium , a common and valuable ingredient of natural cosmetics with skin-lightening and antioxidant properties [ 13 ]. Significant tyrosinase inhibitory properties were also recently described for hydroglycolic extracts from A. biebersteinii , inhibiting both monophenolase and diphenolase activity of this enzyme [ 14 ]. The most common phytoconstituents identified in A. biebersteinii extracts with tyrosinase inhibitory activity were chlorogenic acid, caffeic acid, rutin, quercetin, luteolin, apigenin [ 15 ], caffeoylquinic acid (CQA) isomers: 3-CQA, 4-CQA, 5-CQA, and a dicaffeoylquinic acid derivative: cynarin (1,3-DCQA) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another article by Gaweł-Bęben et al [20], comparative phytochemical and biological activity studies of hydroglycolic extracts from flowering aerial parts of Achillea millefolium (Am) and Achillea biebersteinii (Ab) collected in Kazakhstan were performed. The aim of the study was to evaluate potential cosmetic application of (Ab).…”
mentioning
confidence: 99%